Brass Eagle lectern - Ghosh, Ayan (2023)
A specially crafted brass eagle lectern was donated to the church in memory of Lieutenant General HF Hancock, who served in Mumbai as Under Secretary to the government and as inspector of Railways. Later, he got posted in Kolkata, where he was Secretary of Public Works Department. Hancock died in Calcutta in 1887 at the age of 53. The eagle acts as a symbol of St John, one of the Twelve Apostles.